Codificación de Imagenes Satelitales Utilizando Técnicas de Compresión con perdidas y sin perdidas - Flores Goycochea, Carlos Alberto (2010)
In this work of thesis there appears the development of a technology of codification to achieve the compression of images satelitales, facilitating hereby his transmission on having used minor bandwidth and minor time of transmission, as well as also facilitating his storage on having used devices with minor capacity in bytes. This project is characterized by the implementation of computational algorithms based on the software Matlab, where one has developed two technologies of compression with the purpose of reaching a high degree of compression without altering too much the information contained in the image. They are two technologies combined that are in use in this thesis: the codification with losses, and without losses. The codification with losses is based on the use of transformed discreet of the cosine in 2D (two dimensions), as the JPEG standard uses it, and the codification without losses based on the use of the codification Huffman, where it is achieved to assign the minor quantity of bits for the codification without losing any information. This combination of technologies obtains valuable results especially in images satelitales that are obtained by very poor resolutions in comparison with the conventional photographies